2009
DOI: 10.1097/mol.0b013e3283319127
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in women suffering from familial hypercholesterolemia: a harmful period for both mother and newborn?

Abstract: Altogether, the suggested relationship between severe hypercholesterolemia and enhanced atherosclerosis in offspring and possibly the mother warrants further confirmation and, consequently, studies that focus on therapeutic strategies that can safely lower cholesterol levels during pregnancy in these women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 45 publications
0
29
0
2
Order By: Relevance
“…The combination of an increased aortic lipid accumulation in the neonate was also observed [22]. There is an obvious clinical interest in the primary prevention of hypercholesterolemic mothers affected by familial hypercholesterolemia and their newborn, especially for the management of pregnancy [23]. Translational studies demonstrated that administration during pregnancy of the hypocholesterolemic drug cholestyramine [12] or statins [17] to the hypercholesterolemic mothers may reduce atherogenesis and CVD factors in offspring.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The combination of an increased aortic lipid accumulation in the neonate was also observed [22]. There is an obvious clinical interest in the primary prevention of hypercholesterolemic mothers affected by familial hypercholesterolemia and their newborn, especially for the management of pregnancy [23]. Translational studies demonstrated that administration during pregnancy of the hypocholesterolemic drug cholestyramine [12] or statins [17] to the hypercholesterolemic mothers may reduce atherogenesis and CVD factors in offspring.…”
Section: Introductionmentioning
confidence: 95%
“…Translational studies demonstrated that administration during pregnancy of the hypocholesterolemic drug cholestyramine [12] or statins [17] to the hypercholesterolemic mothers may reduce atherogenesis and CVD factors in offspring. However, the role of statins during pregnancy is contraindicated due to their teratogenicity [23]. Currently, no evidence-based guidelines exist on the optimal clinical approach in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…There is scarce and conflicting evidence on the teratogenic potential of statins and most of the information on drug safety for the fetus is limited to animal studies, a few case reports and retrospective uncontrolled data [Avis et al, 2009]. A study focusing on the toxicity of atorvastatin in pregnant rats and rabbits has shown that only the hightest doses testedwhich were also toxic for the mothers -had harmful effects in pregnancy by increasing postimplantation loss and decreasing fetal body weight [Dostal et al, 1994].…”
Section: Statinsmentioning
confidence: 99%
“…For each pregnancy, a woman with familial hypercholesterolaemia will be without statin therapy for at least 12 -15 months, and often longer, depending on the length of time required to conceive. Several studies show that these women develop very high lipid levels during this period (9,10).…”
Section: Familial Hypercholesterolaemia In Pregnant and Breastfeedingmentioning
confidence: 99%